External speech processing and auditory verbal hallucinations: A systematic review of functional neuroimaging studies. (December 2021) - Richards, Sophie E.; Hughes, Matthew E.; Woodward, Todd S.; Rossell, Susan L.; Carruthers, Sean P.
Highlights: External speech processing deficits are seen in individuals with AVH. We consolidate the functional neuroimaging literature of these deficits. Altered function and coupling of the temporal auditory regions were evident. Some evidence of further limbic, default mode, salience and subcortical involvement. We provide in-depth recommendations for future study designs. Abstract: It has been documented that individuals who hear auditory verbal hallucinations (AVH) exhibit diminished capabilities in processing external speech. While functional neuroimaging studies have attempted to characterise the cortical regions and networks facilitating these deficits in a bid to understand AVH, considerable methodological heterogeneity has prevented a consensus being reached. The current systematic review investigated the neurobiological underpinnings of external speech processing deficits in voice-hearers in 38 studies published between January 1990 to June 2020. AVH-specific deviations in the activity and lateralisation of the temporal auditory regions were apparent when processing speech sounds, words and sentences. During active or affective listening tasks, functional connectivity changes arose within the language, limbic and default mode networks. However, poor study quality and lack of replicable results plague the field. A detailed list of recommendations has been provided to improve the quality of future research on this topic.